Preschool childhood in Ukraine: ethnopedagogical measurement in modern multicultural space - Nelly Lysenko (Vasyl Stefanyk Precarpathian National University, 2017)
The scientific approaches to defining the phenomenon of "childhood" in its social and educational dimension are analyzed in the article; the basic characteristics of childhood as a special state of preschool period of person's development are considered. Key words: childhood, multicultural space, ethnopedagogical measurement.